Leachability of solidified petroleum sludge - Mohd Zain, A. (Trans Tech Publications Ltd, 2014)
Petroleum sludge was solidified in ordinary Portland cement, and the leachability test was performed based on American Nuclear Society 16.1 to produce leachate. The organic in solidified sludge was extracted by micro solid extraction to determine the organic in the sample. Organic in the leachate sample was detected by solid phase micro extraction by head space polydimethyl siloxane fiber using gas chromatography mass spectrometry. The targeted organic compounds in solid sample and leachate were quantified by the benzene, toluene, ethyl benzene, xylene, naphthalene and phenanthrene standards. The organic compounds in solidified sludge consist of aliphatic and ester acid with long carbon chain of Carbon 15 to Carbon 64. The aliphatic group in the leachate was found at the reduced rate of about tenfold of the solid sample. Derivative leachate products mainly composed of cyclic siloxane compounds. The metals leachability in the acidic medium depends on the metal hydroxide solubility value. High lead mobility in the acidic medium was due to its high solubility induced the highest effective diffusion coefficient of 1.59 Ã 10-07cm2/s. Â© (2014) Trans Tech Publications, Switzerland.